The Influence of Sasak Vowels on English Pronunciation: A Study of the Ngeno-Ngene Dialect - Yaqin, Lalu Nurul; Sumaelani, Sumaelani; Fikri, Zaenul; Yusof, Norazmie; Ghazali, Sarah Ahmad (SCAD Independent, 2025)
The study aims to examine the vowel series in the Ngeno-Ngene dialect of the Sasak language, which is commonly spoken by students at universities in Lombok. More specifically, it investigates the number of vowel series and their impact on the pronunciation of English by these students. Data for this study were collected from students at Universitas Gunung Rinjani in Lombok, Indonesia, representing eleven villages in East Lombok. The study used a qualitative method, which included observation and interviews. The findings revealed a total of 22 vowel series in the Ngeno-Ngene dialect. The study also emphasized how these vowel series influence the pronunciation of English by students. It indicates that students tend to carry over vowel sounds from their native language when pronouncing English words with similar vowel series. This effect is attributed to an unsupportive language environment and a lack of opportunities for speaking practice and listening comprehension.